STUDY OF STRENGTH REDUCTION OF REINFORCED CONCRETE BEAM UNDER FIRE TESTS - Fedchenko, S. (Municipal economy of cities. Series: «Economy science», 2023)
The article presents the results of studies of the regularity of changes in the concrete strength of reinforced concrete beams depending on the heating temperature of its inner layers under fire conditions by interpreting the temperature and deformation measurement results. To obtain the data necessary to identify patterns of concrete strength reduction, we developed a method of fire tests that substantiates the experimental base, design, and number of samples, type, number, and location of measuring devices, as well as the method for statistical processing of measurement data. Based on the developed methodology, we conducted fire tests. As a result of the tests, we obtained a set of measurement results in the form of time dependences of temperature indicators at individual cross-section points and the dependence of the maximum beam deflection on time, which are necessary to identify the coefficients of reduction in concrete strength of reinforced concrete beams under fire test conditions. We then used the proposed method to identify regularities in the reduction of concrete strength of a reinforced concrete beam, which includes interpolation using the obtained temperature indicators at individual points of the cross-section of the beam, which allows us to set the temperature at any point of the cross-section at any control time of measurements based on the approximation of isotherms by parabolas with a variable indicator of their degree. At the next stage, to identify the dependence of the concrete strength of reinforced concrete beams, we used a method based on the compilation of systems of equilibrium equations of internal layers in the cross-section of a reinforced concrete beam, in which the unknown values ​​are the coefficients of reduction of concrete strength for a range of temperatures every 100 °С in the range from 20 °С up to 1200 °С, provided that the reduction factor for the specified heating temperature of the inner layer of concrete is determined by linear interpolation. Using the proposed approach, we obtained appropriate results for a reinforced concrete beam subjected to fire tests. The obtained dependences of the strength reduction coefficient were used to evaluate the fire resistance of reinforced concrete beams and crossbars by the calculation method based on the deformation model. By comparing the obtained data with the data from the literature, we established the adequacy of the calculated data based on the relative deviation and Fisher’s test. The totality of the obtained data allows for improving the calculation method for evaluating reinforced concrete crossbars and beams by increasing the accuracy of the data obtained.